Pengaruh Ekstrak Gulma dan Bahan Alami terhadap Pertumbuhan dan Hasil Caisim (Brassica chinensis L.) - Rahayu, Muji; Buruuj Ahwaludin; Andriyana Setyawati; Aprilia Ike Nurmalasari; Amalia Tetrani Sakya; Djoko Purnomo (Jurnal Hortikultura Indonesia, 2023)
The use of allelochemicals as bioherbicides has the potential for environmentally friendly weed control. Research was conducted to determine the effect of weed extracts and natural substances on the growth and yield of Chinese cabbage (Brassica chinensis L.). This study used a Completely Randomized Design (CRD) with weed extract concentration and natural substances as the single factor. There were 16 treatments repeated 3 times, and each treatment consisted of 2 polybags, resulting in a total of 48 experimental units with 96 caisim plants as observed samples. The data that has been collected then analyzed using analysis of variance (ANOVA) and if it shows the significant effect, then it is further tested with the DMRT test at the significant level with α 5%. The results showed that weed extracts and natural ingredients significantly affected plant height 35 DAP, number of leaves 21 DAP, stem fresh weight, fresh weight of plant, and dry weight of plant. Euphorbia heterophylla leaf extract at a concentration of 200 g L-1 was able to increase plant height, and fresh weight of plant, Cyperus rotundus leaf extract at a concentration of 120 g L-1 was able to increase dry weight of plant, while Terminalia catappa extract at a concentration of 200 g L-1 and Melaleunca laucadendron at a concentration of 40 g L-1 was increased the number of leaves at the age of 21 DAP.Keywords: allelochemicals, bioherbicide, concentration, production, vegetable plants